Hedge fund investing : index return persistence and style portfolio performance 1994-2004. - Wong, Pei Ling. (2008)
Our applied research reexamines the index return persistence and the active return performance of hedge fund style portfolios for the period from 1994 to 2004. The monthly return persistence in nine hedge fund indices is measured by Hurst Fractal exponent, and the style portfolio’s monthly performance is evaluated in terms of information ratio.